Physical chemistry - Alberty, Robert A.; Silbey, Robert J. (New York : John Wiley & Son, Inc., 1980)
Describes the basic theory of chemistry from the standpoint of thermodynamics, quantum mechanics and spectroscopy, as well as statistical mechanics, kinetics and macro/microscopic structures. This edition has been revised to include new material on macromolecules and surface dynamics
THERMODYNAMICS; Zeroth Law of Thermodynamics and Equations of State; First Law of Thermodynamics; Second Law and Third Law of Thermodynamics; Gibbs Energy and Helmholtz Energy; Chemical Equilibrium; Phase Equilibrium: One-Component Systems; Phase Equilibrium: Two- and Three-Component Systems; Electrochemical Equilibrium; Ionic Equilibrium and Biochemical Reactions; QUANTUM MECHANICS AND SPECTROSCOPY; Quantum Theory; Atomic Structure; Molecular Electronic Structure; Symmetry; Rotational and Vibrational Spectroscopy; Electronic Spectroscopy of Molecules; Magnetic Resonance Spectroscopy; STATISTICAL MECHANICS AND KINETICS; Statistical Mechanics; Kinetic Theory of Gases; Experimental Kinetics and Gas Reactions; Chemical Dynamics and Photochemistry; Kinetics in the Liquid Phase; MACROSCOPIC AND MICROSCOPIC STRUCTURES; Macromolecules; Solid-State Chemistry; Surface Dynamics; Appendices; Index.
Includes bibliographical references and index.
Keywords: CHEMISTRY, PHYSICAL AND THEORETICAL